Biopolitics, materiality and meaning in modern European drama - Fraunhofer, Hedwig, 1959- (New materialisms (Edinburgh, Scotland), 2020)
Arguing that existing modernisation theories have been unnecessarily one-sided, Hedwig Fraunhofer offers a rewriting of modernity that cuts across binary methodologies - nature and culture, mind and matter, epistemology and ontology, critique and affirmative writing, dramatic and postdramatic theatre.